The Relationship of Family Support to Control Adherence in Hypertension Patients in Hegarmanah Village - Intan Apriliani; Dewi Dolifah; Delli Yuliana Rahmat (NERS Jurnal Keperawatan, 2025)
Hypertension is a chronic disease that is the leading cause of morbidity and mortality worldwide, including in Indonesia. Hypertension management depends on medication and requires patient compliance in undergoing routine check-ups at health facilities. However, the level of compliance among hypertensive patients in undergoing routine check-ups is still relatively low. One factor that influences compliance is family support, which can take the form of emotional, instrumental, informational, or appreciative support. Previous studies have shown a relationship between family support and compliance with hypertension control, but generally still view family support in general terms. Not many studies have examined each aspect of family support (emotional, instrumental, informational, and appreciation) more specifically, especially in areas with high prevalence, such as Hegarmanah Village, which makes this study unique. This study aims to investigate the relationship between family support and adherence to routine check-ups among hypertensive patients in Hegarmanah Village, the service area of the Jatinangor Community Health Center. This study used a descriptive quantitative design with a cross-sectional approach. The population in this study consisted of 357 people, and the sample size used was 85 respondents selected using purposive sampling. The respondents in this study were hypertensive patients living in Hegarmanah Village and registered at the Jatinangor Community Health Center. The inclusion criteria included: (1) diagnosed with hypertension with above-normal blood pressure, (2) undergoing routine health checks at least in the last 3 months, and (3) living with family. The measurement tools used were a family support questionnaire adopted from previous researchers and a check-up compliance questionnaire modified from the Morisky Medication Adherence Scale. The data were analyzed using the chi-squared test. The chi-squared test results showed a p-value <0.001, indicating a significant relationship between family support and patient compliance in controlling hypertension. It was found that respondents with good family support had good control compliance, totaling 19 respondents (24.1%), while those with relatively little family support had low compliance, totaling four respondents (5.1%). Based on Cramer's V value of 0.382, the strength of the relationship between the two variables is in the moderate category. This suggests that the higher the level of family support received by patients, the greater the likelihood of patients complying with hypertension control. Family support plays a significant role in encouraging patients to undergo routine follow-up care. Family-based interventions are expected to be part of health care strategies to improve patient compliance.